The mechanical efficiency of a sweep horse power - Roinson, H.J. (My University, 1897)
Introduction: The mechanical efficiency of any machine or power is the useful work obtained, or in other words it is the work left after the function of the machine parts has been over come. It has become important at this day and age to know the efficiency of machines and powers, because those that are called for are the ones that will do the greatest amount of work with the least friction possible. The object of determining the efficiency of a sweep horse power was to find what percent of the work put into the power was lost by the gearing and bearings of the power. A one horse sweep power was secured and a series of tests made. The power selected was simple in construction, consisting of a master wheel or large bevel gear, which drove a small bevel gear or pinion to which a tumbling rod was attached. The object of the tumbling rod was to transmit the energy to some suitable place where it could be used. A dynamometer was attached to the sweep or lever arm of the power, and the horse allowed to pull on the dynamometer. A dynamometer is a device for measuring the power or force of any motor.
Citation: Roinson, H.J. The mechanical efficiency of a sweep horse power. Senior thesis, Kansas State Agricultural College, 1897.
Morse Department of Special Collections
Keywords: Mechanical engineering; Sweep horse power; Dynamometer; Efficiency; Theses; Manuscripts (documents)